2002
DOI: 10.1002/ijc.10852
|View full text |Cite
|
Sign up to set email alerts
|

Inactivation of the DNA repair gene O6‐methylguanine‐DNA methyltransferase by promoter hypermethylation and its relationship to aflatoxin B1‐DNA adducts and p53 mutation in hepatocellular carcinoma

Abstract: Hepatocellular carcinoma (HCC) is one of the most common human malignant neoplasms with almost 500,000 estimated new cases enumerated worldwide during the most recent year surveyed. 1 Its etiology is not completely clear, but strong associations exist with hepatitis B and C virus infection and several dietary or environmental factors, including aflatoxin B 1 (AFB 1 ). The molecular pathogenesis of HCC appears to involve multiple genetic aberrations in the molecular control of hepatocyte proliferation, differen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
38
0

Year Published

2007
2007
2021
2021

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 77 publications
(39 citation statements)
references
References 24 publications
(28 reference statements)
1
38
0
Order By: Relevance
“…Mutation in p53 was shifted to a G-A mutation by MGMT promoter hypermethylation in colorectal cancer (Esteller et al, 2000), and similar findings were later found for NSCLC (Wolf et al, 2001) and hepatocellular cancer (Zhang et al, 2003). These mutations have been attributed to endogenous deamination of methylated cytosine to thymine.…”
Section: Discussionmentioning
confidence: 68%
See 2 more Smart Citations
“…Mutation in p53 was shifted to a G-A mutation by MGMT promoter hypermethylation in colorectal cancer (Esteller et al, 2000), and similar findings were later found for NSCLC (Wolf et al, 2001) and hepatocellular cancer (Zhang et al, 2003). These mutations have been attributed to endogenous deamination of methylated cytosine to thymine.…”
Section: Discussionmentioning
confidence: 68%
“…MGMT inactivation through promoter hypermethylation was the first example of a repair gene whose expression correlated with a p53 mutation pattern (Esteller et al, 2000;Wolf et al, 2001;Zhang et al, 2003). Mutation in p53 was shifted to a G-A mutation by MGMT promoter hypermethylation in colorectal cancer (Esteller et al, 2000), and similar findings were later found for NSCLC (Wolf et al, 2001) and hepatocellular cancer (Zhang et al, 2003).…”
Section: Discussionmentioning
confidence: 84%
See 1 more Smart Citation
“…Transcriptional silencing of the MGMT gene can be caused by promoter methylation but also by exposure to certain carcinogens. 33 Our findings indicate that MGMT promoter methylation is probably not involved in HCC development and is not a useful molecular marker. This is consistent with previous results by Esteller et al 6 By contrast, Zhang et al found MGMT gene methylation in 39% of HCC and a correlation with aflatoxin B1-exposure.…”
Section: Discussionmentioning
confidence: 71%
“…This is consistent with previous results by Esteller et al 6 By contrast, Zhang et al found MGMT gene methylation in 39% of HCC and a correlation with aflatoxin B1-exposure. 33 These discrepant results might be explained by the influence of aflatoxin B1-exposure in the study population examined. Furthermore, for MGMT gene-promoter methylation analysis, it is important to define the CpG islands to be analyzed as demonstrated by Matsukura et al 34 In contrast to MGMT, APC and DAP-K, the methylation status of the promoter of p16 INK4a and GSTP1, which encodes for the gluthatione S-transferase, show a strong correlation with hepatocarcinogenesis.…”
Section: Discussionmentioning
confidence: 89%